PENGARUH SISTEM INFORMASI MANAJEMEN DAERAH, KUALITAS DATA INPUT, DAN FAKTOR EKSTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN (STUDI EMPIRIS SKPD KOTA MEDAN) - Fauzan, Muhammad; Fachruddin, Rudy (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
The purpose of this research is to examine the effect of SIMDA, Quality of Data, and External Factor on the quality of financial reports. The population of this research is all offices within the ministries and institutions in the Medan region which the sampling technique uses non probability sampling with census method. Respondents who are the object of this research are those who are most responsible for Assets, consisting of goods managers / users and SIMDA application operators, so that 68 respondents are obtained. Data analysis method used is multiple linear regression with the help of SPSS 25. The result of this research shows that (1) SIMDA, Quality of Data, and External Factor has a positive effect on the quality of financial reports, (2) partially SIMDA has a positive effect on the quality of financial reports and (3) partially Quality of Data has a positive effect on the quality of financial reports, (4) partially External Factor has a positive effect on the quality of financial reports